Interferensi Bahasa Sasak terhadap Bahasa Arab Santri - A. Syahid Robbani; Hisyam Zaini (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This research aims to examine the forms of interference of Sasak language to Arabic used by students in the boarding school environment who in their daily practice of Arabic knowledge and the efforts made to overcome the language disorder. This research is qualitative research using descriptive methods. The data in this study was obtained through observations and interviews with students and teachers in Nurul Hakim Boarding School Kediri West Lombok. The results showed that the Arabic language used by students in Nurul Hakim Boarding School Kediri West Lombok, in reality, is still heavily influenced by their mother tongue, Sasak. The interference is spread across several aspects such as phonology, morphology, syntax, and lexicon. Various forms of language interference are tried to be minimized by teachers by holding muhadatsah activities that are routinely carried out, teaching Arabic grammar both in school and in dormitories, and requiring students to memorize Arabic vocabulary that is regularly updated every week.